2023
DOI: 10.1108/jocm-11-2021-0354
|View full text |Cite
|
Sign up to set email alerts
|

The role of human resource management practices on the results of digitalisation. From Industry 4.0 to Industry 5.0

Abstract: PurposeThis article aims to analyse the impact of data analytics and robots on firms' performance across Europe.Design/methodology/approachThis paper aims to examine the impact of data analytics and robots on companies' performance, multilevel models are estimated. Empirical research is based on the fourth round of the European Company Survey 2019.FindingsThe main findings show that human resource management practices (HRMP) are relevant to explain firms' profits. Therefore, human resource practices and techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 57 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…In terms of prioritizing workers welfare and wellbeing (Dinorah et al ., 2022), carried out a research within the context of industry 5.0 and found that job satisfaction in the Czech Republic did not decline during the pandemic. Moreover, Erro-Garcés and Aramendia-Muneta (2023) reported that the adoption of industry 5.0 ie a blend of human resources and digital technologies led to higher employee and organizational performance in European firms.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of prioritizing workers welfare and wellbeing (Dinorah et al ., 2022), carried out a research within the context of industry 5.0 and found that job satisfaction in the Czech Republic did not decline during the pandemic. Moreover, Erro-Garcés and Aramendia-Muneta (2023) reported that the adoption of industry 5.0 ie a blend of human resources and digital technologies led to higher employee and organizational performance in European firms.…”
Section: Introductionmentioning
confidence: 99%